Development of a Web-Based Correspondence Information System to Enhance Administrative Services in Higher Education - Misna Asqia (AI Society & STMIK Indonesia, 2023)
The administrative services for higher education have been greatly affected by the COVID-19 pandemic. This has also impacted STT-NF. Services to students, such as handling documents that previously required physical presence on campus, now transitioned to an online method. STT-NF has utilized the G-Suite service to facilitate online administrative services for students. However, G-Suite has its limitations, necessitating the development of a Document Submission Information System. The chosen development method for this system is a website employing the Waterfall methodology. After conducting observations and interviews with relevant stakeholders, we identified five issues that the document submission information system had experienced. There are three actors involved. From the previously identified issues, we derived eight solution analyses. Testing was conducted using the Blackbox method for the 11 document submission information system features. The testing results indicate that all features are functioning as intended and have passed successfully.